Effect of Subinhibitory Concentrations of Antibiotics and Disinfectants on ISAba-Mediated Inactivation of Lipooligosaccharide Biosynthesis Genes in Acinetobacter baumannii - Héctor Olmeda-López; Andrés Corral-Lugo; Michael J. McConnell (MDPI AG, 2021)
Inactivation of the lipooligosaccharide (LOS) biosynthesis genes lpxA, lpxC and lpxD by ISAba insertion elements results in high-level resistance to colistin in A. baumannii. In the present study, we quantify the rate of spontaneous insertional inactivation of LOS biosynthesis genes by ISAba elements in the ATCC 19606-type strain and two multidrug clinical isolates. Using insertional inactivation of lpxC by ISAba11 in the ATCC 19606 strain as a model, we determine the effect of several subinhibitory concentrations of the antibiotics, namely tetracycline, ciprofloxacin, meropenem, kanamycin and rifampicin, as well as the disinfectants ethanol and chlorhexidine on ISAba11 insertion frequencies. Notably, subinhibitory concentrations of tetracycline significantly increased ISAba11 insertion, and rifampicin completely inhibited the emergence of colistin resistance due to ISAba11 inactivation of lpxC. Sequencing of ISAba11 insertion sites within the lpxC gene demonstrated that insertions clustered between nucleotides 382 and 618 (58.3% of unique insertions detected), indicating that this may be a hotspot for ISAba11 insertion. The alignment of insertion sites revealed a semi-conserved AT-rich consensus sequence upstream of the ISAba11 insertion site, suggesting that ISAba11 insertion sites may be sequence-dependent. This study explores previously uncharacterized aspects regarding the acquisition of colistin resistance through insertional activation in LOS biosynthesis genes in A. baumannii.